Spectroscopic analysis of AgI-DNA complex - Oda, Shuji; Komuro, Tomoyuki; Kondo, Yoshinori; Ono, Akira; Tanaka, Yoshiyuki (Nucleic Acids Symposium Series, 2006)
It has recently been reoprted that C-C mismatches were able to recognize AgI specifically, and form AgI-mediated cytosine-cytosine base pairs (C-AgI-C pair). In this study, we explored DNA sequences, which are appropriate for structural studies of this new type of metal-mediated base pairs. For this experiments, we synthesized four kinds of DNA duplexes including a single C-C mismatch. By using UV spectra, we performed titration experiments of DNA duplexes with AgNO3. Within the sequences we tested, it was found that the DNA duplex: 5′-CGCGCGTCC-3′ • 5′-GGACCCGCG-3′ showed 1:1 complexation of this DNA duplex and AgI. In addition, a DNA duplex: 5′-TAAATCTAATA-3′ • 5′-TATTACATTTA-3′ also exhibited a similar character. Therefore, these two DNA duplexes are interesting candidates for structural analyses.